Does the school fruit and vegetable scheme improve children's diet? A non-randomised controlled trial. Issue 8 (13th July 2007) - Ransley, J K; Greenwood, D C; Cade, J E; Blenkinsop, S; Schagen, I; Teeman, D; Scott, E; White, G; Schagen, S
Abstract : Objective: Evaluation of the impact on diet of the school fruit and vegetable scheme (SFVS). Design: Non-randomised controlled trial. Setting: Infant and primary schools in the north of England. Participants: 3703 children aged four to six years (reception, year 1, and year 2). Intervention: One portion of fruit or vegetable provided per child on each school day between February and December 2004. Main outcome measures: Fruit and vegetables consumed and intake of nutrients. Results: The SFVS was associated with an increase in fruit intake across reception and year 1 pupils of 0.4 portions (95% confidence interval, 0.2 to 0.5) and 0.6 portions (0.4 to 0.9), respectively, at three months, which fell to 0.2 (0.1 to 0.4) and 0.3 (0.1 to 0.6) at seven months. In year 2 it was associated with an increase of 0.5 portions (0.2 to 0.7) of fruit at three months, which fell to baseline values at seven months when these children were no longer eligible for the scheme. Overall, at seven months there were no changes in vegetable consumption, no associations between the SFVS and energy, fat, or salt intake, and small changes in carotene and vitamin C intake. Conclusions: The SFVS promoted an increase in fruit intake after three months. At seven months the effect remained significant but reduced, and it returned to baseline in year 2 when pupils were no longer part of the scheme. There was a small impact on the intake of some nutrients across the children surveyed.